Caspase inhibitors in drug discovery - O'Brien, Tom (Henry Stewart Talks, 2007)
Apoptotic caspases, Inflammatory caspases, Validation of caspase involvement in disease, Animal models, Rheumatoid arthritis, Liver degeneration, Small molecule drug discovery, Inhibitor specificity, Reversible and irreversible binding inhibitors, Clinical trial data
Archived at 2021/02/25